Effects of the beam offset on microstructure and properties of electron beam welded tantalum and Inconel 718 joints. (30th April 2021) - Jia, Shudang; Li, Dong; Tao, Fu; Fan, Linhao; Chen, Jieshi
Abstract: In this paper, electron beam welding of tantalum and Inconel 718 superalloy was performed. The formability, microstructure, defect characteristics and mechanical properties of joints were investigated by controlling the position of the electron beam. The weld zone of tantalum and Inconel 718 joints was mainly composed of columnar crystals and dendrites during the welding of non-beam offset and 0.5 mm beam offset to tantalum. The reaction layer composed of a large number of intermetallic compounds was found on the tantalum side, and it was the place where the fracture occurred. Tensile strength of the joints was 313 MPa and 138 MPa, respectively, and the joints exhibited brittle fracture mode due to the formation of voids and cracks in the reaction layer. The microhardness of the weld zone was higher than that of the base metal due to the strengthening effect of tantalum. Fortunately, when the beam deviated by 0.5 mm to the Inconel 718 side, equiaxed grains formed in the weld zone, and the morphology of the reaction layer changed, which improved the toughness of the joint. The tensile strength of the joint reached 480 MPa under the condition of 0.5 mm beam deviated to the Inconel 718 side.